Associations of Two Ecologically Significant Social Insect Taxa in the Litter of an Amazonian Rainforest: Is There a Relationship between Ant and Termite Species Richness? - Amy L. Mertl; James F. A. Traniello; Kari Ryder Wilkie; Reginaldo Constantino (Psyche: A Journal of Entomology)
In spite of the ecological dominance of Neotropical ants and termites, little is understood about how their interactions influence their species richness and distribution. We surveyed ground-dwelling termite and ant species in a primary rainforest in Ecuador and analyzed ecological correlates of diversity. Termite richness was positively correlated with ant richness and abundance of twig-nesting ants. We found no evidence of competition for twigs between termites and ants. No ecological factors were correlated with termite diversity although elevation and twig and log abundance influenced ant diversity. When ant richness was compared to the richness of termites employing different predator defenses, a positive correlation was found with soldierless termites, but not genera employing chemical or mechanical defense. Our results suggest that multiple ecological factors influence ant and termite diversity, and that ant predation on termites may have a greater effect than competition between ant and termites for nest sites and food sources.